A Methodical Review on Carbon-Based Nanomaterials in Energy-Related Applications - Robert Birundu Onyancha; Kingsley Eghonghon Ukhurebor; Uyiosa Osagie Aigbe; Otolorin Adelaja Osibote; Heri Septya Kusuma; Handoko Darmokoesoemo (Adsorption Science & Technology)
Carbon nanomaterials are endowed with novel and magnificent optical, electrical, chemical, mechanical, and thermal properties, with a promising prospect in different advanced applications such as electronics, batteries, capacitors, wastewater treatment, membranes, heterogeneous catalysis, and medical sciences. However, macroscopic synthesis of carbon materials for industrial use has been a great challenge. Furthermore, structural nonhomogeneity and indefinite fabrication have hindered vigorous and consistent implementation of these materials in extensive technologies. Nevertheless, they offer exotic physics, and as a result, they have continued to attract great interest from the scientific community in an effort aimed to optimize their properties through innovative synthesis techniques, ensuring macroscopic production and discovering new applications. Hence, this study endeavours to provide a conscious review of these materials via the comprehensive discussion of the various allotropes of carbon (fullerenes, carbon nanotubes, and graphene), synthesis techniques (arc discharge, laser ablation, and chemical vapor deposition), and their applications in energy-related fields (batteries, capacitors, photocells, hydrogen storage, sensors, etc.) and their impending prospects.